Systematic review: the consequences of psychosocial effects of inflammatory bowel disease on patients′ reproductive health. Issue 11 (8th November 2018) - Purewal, Satvinder; Chapman, Sarah; Czuber‐Dochan, Wladyslawa; Selinger, Christian; Steed, Helen; Brookes, Matthew J.
Summary: Background: High levels of voluntary childlessness and pregnancy‐related fears have been reported amongst inflammatory bowel disease (IBD) patients. Aims: To investigate what factors determine IBD patients' childbearing decisions; and to examine psychosocial consequences of IBD on various aspects of patients' reproductive health. Methods: Six electronic databases were searched in a pre‐specified and structured manner. Results: A total of 41 articles with data on 7122 patients were included. Between one‐fifth to one‐third of IBD patients had chosen voluntary childlessness. Around 50% of all IBD patients have poor knowledge of pregnancy‐related issues in IBD. Poor knowledge of pregnancy‐related issues in IBD was associated with voluntary childlessness. Observational studies have found preconception counselling is associated with patients choosing parenthood. Pregnancy‐related fears and concerns are multifaceted, stemming partly from lack of knowledge of pregnancy‐related issues in IBD. Many female patients are considered at increased risk for pregnancy because between one‐fifth to one‐third of patients do not use contraception. Research evidence for sexual dysfunction after disease diagnosis and treatment is inconsistent. There are limited data on patients' pregnancy, postpartum and parenting experiences. A few shortcomings of the literature are evident; sample sizes were small, participation rates were low, use of non‐validated questionnaires was common, and few studies included men and/or ethnic minority groups. The design of intervention studies is also weak. Conclusion: This review recommends pre‐conception counselling for all IBD patients of childbearing age to tackle poor knowledge and allow patients to make an informed decision on their reproductive health.